2002
DOI: 10.1103/physreve.66.060101
|View full text |Cite
|
Sign up to set email alerts
|

Trapping reactions with randomly moving traps: Exact asymptotic results for compact exploration

Abstract: In a recent Letter Bray and Blythe have shown that the survival probability PA(t) of an A particle diffusing with a diffusion coefficient DA in a 1D system with diffusive traps B is independent of DA in the asymptotic limit t → ∞ and coincides with the survival probability of an immobile target in the presence of diffusive traps. Here we show that this remarkable behavior has a more general range of validity and holds for systems of an arbitrary dimension d, integer or fractal, provided that the traps are "com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
74
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 30 publications
4
74
0
Order By: Relevance
“…An interesting extension of our model may be a situation in which the target itself moves randomly. It is known, however, that if this motion is diffusive (or sub-diffusive) in low dimensions, the long-time asymptotic form of the probability P N is exactly the same as when the target is immobile (see [22] and also [23,24]). Consequently, in low dimensions in the large-N limit, the search for a diffusive (or sub-diffusive) target by searchers performing intermittent random walks will proceed in exactly the same way as determined in this paper for the case of an immobile target.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting extension of our model may be a situation in which the target itself moves randomly. It is known, however, that if this motion is diffusive (or sub-diffusive) in low dimensions, the long-time asymptotic form of the probability P N is exactly the same as when the target is immobile (see [22] and also [23,24]). Consequently, in low dimensions in the large-N limit, the search for a diffusive (or sub-diffusive) target by searchers performing intermittent random walks will proceed in exactly the same way as determined in this paper for the case of an immobile target.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some very interesting and unexpected results have been established for trapping A + B → B reactions involving randomly moving species [25,26], which have resolved, at least in part, this problem. It has been shown that in one or two dimensions [25], or more generally in systems, in which the fractal dimension of the B particle trajectories is greater than the dimension d of the embedding space [26], (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if the tracer particle is static, this problem is known as the target annihilation problem [7]. Of particular interest is the case when the tracer particle itself has a diffusive motion, a problem that was first studied by Bramson and Lebowitz [8] and has recently seen a flurry of activity [9][10][11][12][13]. It is, however, somewhat frustrating that, despite various new developments, this diffusive target annihilation problem has defied a direct exact solution.…”
mentioning
confidence: 99%
“…(βR), (12) where R = | R|, φ is the angle between R and the z axis, P l (x) is the Legendre polynomial of degree l and K ν (x) is the modified Bessel function of index ν. The unknown coefficients b l are determined from the boundary condition P st (R = a) = 1.…”
mentioning
confidence: 99%